EFEKTIFITAS FORMULA “SUPROMIN” (MAKANAN ENTERAL DARI TEMPE) TERHADAP PERBAIKAN KADAR ALBUMIN DAN KOLESTEROL PASIEN STROK - Sri Sulistiyaningsih; Budiyanti Wiboworini; Ida Nurwati (GIZI INDONESIA, 2022)
Stroke has been a leading cause of death in Indonesia based on Riskesdas data in 2018, it is known that Sroke's prevalence increased from 7 per million to 10.9 per million. Patients with acute stroke were found to be lacking in protein energy by 16.3 percent - 35 percent. "Supromin" is a modified enteral food made from tempeh, skim milk, and egg white which is expected to increase food intake and improve the lipid profile of stroke patients. This study aims to analyze the effect of "supromin" and commercial formulas on albumin and cholesterol levels in stroke patients. This experimental study employed the pre-test and post-test control group design. Respondents were selected using consecutive random sampling. Data were analyzed using paired – t-tests. After 10 days of treatment, there was an increase in albumin levels of 0.17+0.29 mg/dL (p=0.069) in the group receiving the supromin formula and a decrease in albumin levels of 0.08+0.08 mg/dL (p=0.006) in the group receiving the commercial formula. Supromin formula is effective in reducing cholesterol level 16.58+18.31 mg/dL (p = 0.009). Giving supromin formula increases albumin levels and significantly lowers cholesterol levels in stroke patients. It is necessary to consider the provision of the supromin formula for a longer period.